Kesiapan Menikah Generasi Muda: Tinjauan Psikologi Pendidikan Islam - Hidayah, Nur; Rohimah, Siti (Lembaga Yasin AlSys, 2026)
Marriage in Islam is a sacred bond that is not only biological and social in nature but also carries spiritual and educational dimensions; however, in practice, many young people enter marriage without adequate preparedness, leading to various household problems. This article aimed to analyze the concept of marital readiness among young people from the perspective of Islamic educational psychology. This study employed a qualitative approach using a library research method through analysis of primary and secondary sources, including the Qur’an, hadith, books, and relevant scholarly articles. The findings indicate that marital readiness in the perspective of Islamic educational psychology encompasses integrated psychological, emotional, social, economic, and spiritual readiness. Islamic education plays an important role in shaping personality maturity, emotional regulation, understanding of Islamic values, and awareness of moral responsibilities in married life. Thus, marital readiness is understood not merely as readiness in terms of age or material resources, but as the outcome of an ongoing process of value education. This article is expected to provide a theoretical contribution to the development of Islamic educational psychology studies and to serve as a practical reference for premarital guidance and counseling for young people.Marital Readiness; Young People; Islamic Educational Psychology; Islamic Education; Premarital Guidance